Protection of Indigenous Forests from Oligarchy Hegemony - Nur Aida; Muhani Jibi (CV. Rayyan Dwi Bharata, 2023)
The form of government responsibility towards local wisdom values is ideally based on juridical and philosophical. Local wisdom is not seen as a mere cultural product, therefore the government's responsibility for the local wisdom values of indigenous and tribal peoples must be packaged as a comprehensive policy. The aim of this research is expected to be able to provide input to stakeholders, especially the Government and Customary Law Communities in completing the management of customary forest areas, so that justice and prosperity for indigenous peoples can be realized according to the needs of indigenous peoples. The method used in this research is descriptive evaluative research method, in which this study only describes the facts found in the field without making changes to each research variable. The results of the study, the ideal implementation of legal regulations must be adjusted based on the needs of the community. In building a customary forest scheme, Indigenous Peoples must be able to convince the Government and Traditional Leaders to show their ability, local wisdom and seriousness in protecting customary forest areas. Campaigns for customary forest schemes must be carried out systematically as sovereignty and dignity for the purity of identity independently in order to save customary forests and their potential. As long as the consequences of the policy are not detrimental to legal policy, then the customary forest management scheme developed by indigenous and tribal peoples can be justified. In conclusion, it is hoped that in the customary forest scheme there will be certainty in the process of transforming knowledge about traditional values with various local wisdoms and the utilization of agricultural products and the natural environment with a balance based on natural sustainability, without being controlled by oligarchic hegemony.